Effects of anti-TNF-α treatment on lipid profile in rheumatic diseases: an analytical cohort study. Issue 1 (December 2016) - Hassan, Shadi; Milman, Uzi; Feld, Joy; Eder, Lihi; Lavi, Idit; Cohen, Shai; Zisman, Devy
Abstract Background The aim was to assess the influence of long-term treatment with tumor necrosis factor alpha (TNF-α) inhibitors on total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and atherogenic index (AI) in rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS) patients. Methods A retrospective cohort study was conducted on RA, PsA, and AS patients treated with TNF-α inhibitors for at least 270 days between 2001 and 2011. Levels of TC, TG, LDL, and HDL and the AI were compared with baseline values at 0–6, 6–12, 12–18, and 18–24 months. Patients were further subdivided into three groups according to their HMG CoA reductase inhibitor (statin) treatment status in order to assess their effect on the results. Results The records of 311 patients (152 RA, 90 PsA, and 69 AS) were reviewed. TC and TG increased following treatment with TNF-α inhibitors, from 180.85 ± 2.12 mg/dl and 116.00 ± 3.55 mg/dl at baseline to 188.12 ± 2.35 mg/dl (p = 0.02) and 132.02 ± 4.63 mg/dl at 0–6 months (p < 0.01), respectively, and to 184.88 ± 2.09 mg/dl (p = 0.02) and 129.36 ± 4.32 mg/dl at 18–24 months (p < 0.01), respectively. AI increased following treatment with TNF-α inhibitors, from –0.032 ± 0.017 at baseline to 0.004 ± 0.019 at 18–24 months (p < 0.01). LDL decreased significantly in patients who were treated with statins before and during the entire study period, from 119.97 ± 2.86 mg/dl at baseline to 104.02 ± 3.57 mg/dl at 18–24 months (p < 0.01), in contrast to an increase in LDL values in patients who did not receive statins during the study. Conclusions TNF-α inhibitor treatment was associated with a significant increase in TC and TG levels and the AI. Adding statins to the treatment was associated with a significant decrease in LDL levels.